The Size and Development of the Shadow Economies of 22 Transition and 21 OECD Countries - Friedrich G. Schneider (Institute for the Study of Labor (IZA), 2002)
Using the currency demand and DYMIMIC approaches estimates are presented about the size of the shadow economy in 22 Transition and 21 OECD countries. Over 2001/2002 in 21 OECD countries is the average size of the shadow economy (in percent of official GDP) 16.7% of ?official? GDP and of 22 Transition countries 38.0%. The average size of the shadow economy labor force (in percent of the population of working age) of the year 1998/99 in 7 OECD-countries is 15.3% and in 22 Transition countries is 30.2%. An increasing burden of taxation and social security contributions combined with rising state regulatory activities are the driving forces for the growth and size of the shadow economy (labor force).
Keywords: O5; O17; H2; D78; H26; 330; shadow economy; transition economies; tax and social security burden; government regulation; Schattenwirtschaft; Ökonometrisches Modell; Schätzung; Osteuropa; OECD-Staaten; DYMIMIC